1993
DOI: 10.1107/s0021889892008744
|View full text |Cite
|
Sign up to set email alerts
|

Twinning of LaGaO3single crystals

Abstract: LaGaO3 single crystals, grown by the method of zone melting without a crucible, with radiation heating, were investigated by X-ray topography and diffractometry. It has been found that at 293 K these crystals have an orthorhombic unit cell with a = 5.520(2), b = 5.490(2), c=7.770 (I)A and twinning in the { 110}/(IT0) and { 112}/(1]-0) systems simultaneously. Regions of cross-twinning have been discovered in these systems. A first-order phase transition from orthorhombic to rhombohedral has been observed at 412… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…12 Some authors 13 have suggested a considerable higher temperature (875 • C) for the phase transition, but recent studies 1,14 are in agreement with the lower transition temperature. A second-order phase transition from rhombohedral to monoclinic structure has also been suggested 15 in the temperature range ∼750 to ∼1000 • C. The melting point of LaGaO 3 is 1800 • C. 12 The appearance of twins is common in the perovskite and related structures. It should be noted that although the coefficient of thermal expansion (CTE) for LaGaO 3 above the transition temperature provides an ideal lattice match for high temperature superconducting films, the presence of the disruptive low-temperature phase transition and a strong tendency for twinning restrict its wider application as a substrate material.…”
Section: Crystal Structurementioning
confidence: 95%
“…12 Some authors 13 have suggested a considerable higher temperature (875 • C) for the phase transition, but recent studies 1,14 are in agreement with the lower transition temperature. A second-order phase transition from rhombohedral to monoclinic structure has also been suggested 15 in the temperature range ∼750 to ∼1000 • C. The melting point of LaGaO 3 is 1800 • C. 12 The appearance of twins is common in the perovskite and related structures. It should be noted that although the coefficient of thermal expansion (CTE) for LaGaO 3 above the transition temperature provides an ideal lattice match for high temperature superconducting films, the presence of the disruptive low-temperature phase transition and a strong tendency for twinning restrict its wider application as a substrate material.…”
Section: Crystal Structurementioning
confidence: 95%
“…The domain structure of the single crystals has been investigated by the methods of X-ray angular y-2y and y-scanning topography [16]. In these methods the sample is rotated at an angular rate o.…”
Section: Crystal Characterization Methodsmentioning
confidence: 99%
“…X-ray topography [29,32,34] allowed to find the orientation of domain states or the composition planes between domains. Various models of domain pairs have been developed to explain the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroic domain structures have been investigated in a large number of chemical compositions with the structure of the GdFeO 3 type: natural and synthetic CaTiO 3 crystals [12,[25][26][27][28], (Mg,Fe)SiO 3 [14,26], CaGeO 3 , MnGeO 3 , SmAlO 3 [14], LaGaO 3 [29][30][31][32][33][34], NdGaO 3 [8,35].…”
Section: Introductionmentioning
confidence: 99%